Sarcospan protects against LGMD R5 via remodeling of the sarcoglycan complex composition in dystrophic mice - Mokhonova, Ekaterina I.; Helzer, Daniel; Malik, Ravinder; Mamsa, Hafsa; Walker, Jackson; Maslanka, Mark; Fleser, Tess S.; Afsharinia, Mohammad H.; Liu, Shiheng; Holmberg, Johan; Zhou, Z. Hong; Deeds, Eric J.; et al. (Journal of Clinical Investigation, 2025)
The dystrophin-glycoprotein complex (DGC) is composed of peripheral and integral membrane proteins at the muscle cell membrane that link the extracellular matrix with the intracellular cytoskeleton. While it is well established that genetic mutations that disrupt the structural integrity of the DGC result in numerous muscular dystrophies, the 3D structure of the complex has remained elusive. Two recent elegant cryoEM structures of the DGC illuminate its molecular architecture and reveal the unique structural placement of sarcospan (SSPN) within the complex. SSPN, a 25 kDa tetraspanin-like protein, anchors β-dystroglycan to the β-, γ- and δ-sarcoglycan trimer, supporting the conclusions of biochemical studies that SSPN is a core element for DGC assembly and stabilization. Here, we advance these studies by revealing that SSPN provides scaffolding in δ-sarcoglycanopathies, enabling substitution of δ-sarcoglycan by its homolog, ζ-sarcoglycan, leading to the structural integrity of the DGC and prevention of limb-girdle muscular dystrophy R5. Three-dimensional modeling reveals that ζ-sarcoglycan preserves protein-protein interactions with the sarcospan, sarcoglycans, dystroglycan, and dystrophin. The structural integrity of the complex maintains myofiber attachment to the extracellular matrix and protects the cell membrane from contraction-induced damage. These findings demonstrate that sarcospan prevents limb-girdle muscular dystrophy R5 by remodeling of the sarcoglycan complex composition.